PENGARUH METODE CARD SORT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADITS - Fauzi, Anis; Mashuri, Imam; Priwanto, Deni Arjun; Hakeem, Altan (INCARE, International Journal of Educational Resources, 2022)
This study examines the effect of the card sort method on student learning outcomes, which is motivated by the low learning outcomes of class VII students in the Al-Qur'an Hadith subject at MTs Kebunrejo Genteng. This study aims to determine the effect of the Card Sort method on learning outcomes of Al-Qur'an Hadith class VII E at MTs Kebunrejo Genteng. The type of research used is the Pre-Experimental Design type of One Group Pretest-Posttest with a quantitative approach. The sample in this study were class VII students of MTs Kebunrejo Genteng with a total sample of 28 students from 189 populations, with the sampling technique using a non-probability sampling technique with purposive sampling. Data collection techniques in this study used observation, interviews, tests and documentation. The research data were obtained from the results of a multiple choice written test consisting of 20 items with two categories of Pretest and Posttest. The results of the research obtained from learning the Al-Qur'an Hadith subject using the Card Sort method obtained a t-count value of 17.261 with a t-table value (dk = n-1 = 28-1 = 27) of 2052. With a value it is known that the t-table value ? t-count value (2052 ? 17.261), it can be said that Ho is rejected and Ha is accepted with a significance value of Sig. 2 tailed by 0.000. So it can be concluded that there is an effect of using the Card Sort method on student learning outcomes in class VII E at MTs Kebunrejo Genteng Banyuwangi. With a t-test correlation value of 0.674.